Kinetic Investigation of Peroxide Decomposition by Calorimetry under High‐Pressure. Issue 3 (3rd January 2020) - Sartorius, Jana; Busch, Markus
Abstract: Radical polymerization is widely applied in industrial production using peroxides as initiators. The high‐pressure polymerization process of LDPE is evaluated of pressures up to 3500 bar and temperature up to 300 °C. For simulations physical properties and kinetics under these harsh conditions have to be measured. Therefore, kinetic parameters such as activation energy, pre‐exponential factor and order of reaction as well as their dependence on pressure and solvent are investigated in this study with high‐pressure calorimetry using a transitiometer and DSC using high‐pressure crucibles. Abstract : Di‐ tert‐ butyl peroxide (DTBP) is an initiator for radical polymerisation carried out at harsh conditions, thus, the influence of pressure up to 1000 bar is studied. Therefore, kinetics of DTBP decomposition are investigated by high‐pressure calorimetry evaluating with Kissinger and Borchardt‐Daniels method and using acetone, ethylbenzene, isododecane and LDPE as solvent.